2003
DOI: 10.1161/01.res.0000095977.66660.86
|View full text |Cite
|
Sign up to set email alerts
|

Cell Coupling Between Ventricular Myocyte Pairs From Connexin43-Deficient Murine Hearts

Abstract: Abstract-Mice with cardiac-restricted inactivation of the connexin43 gene (CKO mice) have moderate slowing of ventricular conduction and lethal arrhythmias. Mechanisms through which propagation is maintained in the absence of Cx43 are unknown. We evaluated gap junctional conductance in CKO ventricular pairs using dual patch clamp methods. Junctional coupling was reduced to 4Ϯ2 nS (side-to-side) and 11Ϯ2 nS (end-to-end), including 21% of cell-pairs with no detectable coupling, compared with 588Ϯ104 nS (side-to-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
70
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 55 publications
10
70
2
Order By: Relevance
“…Germline deletion of the Cx43 gene in mice leads to perinatal lethality due to developmental cardiac malformation 30 . In contrast, mice with cardiac-restricted inactivation of Cx43 are viable; however, they develop ventricular tachyarrhythmias leading to sudden cardiac death within 2 months 50,51 . Several mutations in Cx43 have previously demonstrated serious conduction abnormalities both in mouse models and in human patients 47,[52][53][54][55] .…”
Section: Discussionmentioning
confidence: 99%
“…Germline deletion of the Cx43 gene in mice leads to perinatal lethality due to developmental cardiac malformation 30 . In contrast, mice with cardiac-restricted inactivation of Cx43 are viable; however, they develop ventricular tachyarrhythmias leading to sudden cardiac death within 2 months 50,51 . Several mutations in Cx43 have previously demonstrated serious conduction abnormalities both in mouse models and in human patients 47,[52][53][54][55] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Cx43, which contributes to intercellular communication and electrical coupling, is the principal component of ventricular gap‐junction proteins. Genetically engineered Cx43‐deficient (Cx43 +/− or Cx43 −/− ) mice have been reported to be markedly susceptible to ischemia‐induced ventricular tachycardia 36, 37, 38. Ando et al39 reported that increased vagal tone could prevent the loss of Cx43 during acute MI and thus exert antiarrhythmogenic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, animal studies provide compelling evidence that reduced expression of connexin 43 accelerates the onset and increases the incidence, frequency, and duration of ventricular tachyarrhythmias [45]. Mice deficient in connexin 43 not only experienced more spontaneous ventricular arrhythmias, but also VT could be more easily induced when compared to wild-type control mice [46,47]. Despite this compelling evidence of the critical role of connexins in arrhythmogenesis, contemporary research in this field has so far focused on evaluating altered expression of connexin mRNA in patients with HF and there have been no systematic studies performed to identify common connexin genetic variants in cohort populations at high-risk for SCD.…”
Section: Intercellular Cell-to-cell Electrical Couplingmentioning
confidence: 99%